Age at menarche and risk of developing migraine or non-migraine headaches by young adulthood - Hoque, Mohammed Aynul; Siddiqua, Quazi Aysha; Islam, M. Tariqul; Dutta, Surajit; Islam, M. Mazharul; Rassel, Mohammad Aftab; Ferdous, Riasona; Habib, Mansur (International Journal of Research in Medical Sciences, 2025)
Background: Menstruation plays a significant role in the onset of migraine attacks in women, particularly during reproductive years. Among menstrual factors, age at menarche appears to influence migraine prevalence. However, limited research has been conducted on this association in both national and international contexts. This study aimed to assess the relationship between age at menarche and the risk of developing migraine or non-migraine headaches in young adult women attending a tertiary care hospital. To investigate the association between age at menarche and headache type and to compare the clinical characteristics (frequency, duration and severity) of migraine and non-migraine headaches. Methods: This observational study was conducted over two years at the Department of Neurology, Dhaka Medical College Hospital. Women aged >18 years with a history of headache and attending the “Headache Clinic” were included after obtaining informed written consent. Migraine and non-migraine headaches were diagnosed according to ICD-IIIβ criteria. An age-matched control group was also recruited. A total of 300 participants were interviewed (100 in each group: migraine, non-migraine and control). Data were analyzed using SPSS version 22.0. Results: The mean participant age was 30.64±7.78 years. Migraine patients had an earlier mean age at menarche (12.58±1.73 years) than non-migraine (13.66±1.01) and control groups (13.19±0.73) (p<0.001). A 1-year delay in menarche reduced migraine risk by 30% but increased non-migraine headache risk by 83%. Migraineurs experienced more nausea, vomiting and photophobia (p<0.001). Conclusions: Early menarche is associated with an increased risk of migraine in young adult women.